2011
DOI: 10.1111/j.1471-6712.2011.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Risks with older adults in acute care settings: UK occupational therapists’ and physiotherapists’ perceptions of risks associated with discharge and professional practice

Abstract: Internationally, there is evidence that hospital discharge to home for older adults is a complex and challenging process that is dependent upon multidisciplinary team working. At the centre of the discharge process is the management of risk, which involves occupational therapists and other healthcare professionals managing perceived dangers and determining why some dangers are seen as presenting risks while others are not. This study did not aim to explore interprofessional differences but to ascertain a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…Three articles detailing the nature of practice in acute care identified that therapists felt their practices were predominantly defined by their ability to provide a safe and timely discharge home for patients (Blaga & Robertson, 2008;Craig et al, 2004;Griffin & McConnell, 2001). To facilitate this, therapists often completed or referred for a home assessment to identify risks, observe client function and make safety recommendations (Atwal, McIntyre & Wiggett, 2012;Crennan & MacRae, 2010). Concepts of risk and acceptable levels of discharge risk were researched by Atwal, Wiggett & McIntyre, (2011).…”
Section: Thematic Analysismentioning
confidence: 99%
“…Three articles detailing the nature of practice in acute care identified that therapists felt their practices were predominantly defined by their ability to provide a safe and timely discharge home for patients (Blaga & Robertson, 2008;Craig et al, 2004;Griffin & McConnell, 2001). To facilitate this, therapists often completed or referred for a home assessment to identify risks, observe client function and make safety recommendations (Atwal, McIntyre & Wiggett, 2012;Crennan & MacRae, 2010). Concepts of risk and acceptable levels of discharge risk were researched by Atwal, Wiggett & McIntyre, (2011).…”
Section: Thematic Analysismentioning
confidence: 99%
“…In the qualitative paradigm, vignettes are used for different purposes, one of which is to allow for situational context (Hazel, 1995) and are invaluable as a research tool when respondents have not had (or cannot remember) their own personal experience with the issue or situation at hand (Reynold, 2002). Vignettes are commonly used as a way to explore individuals’ decision making strategies among patients (Anthony, 2007; Swenson, Zettler, & Lo, 2006; Vellinga, Smith, Van Leeuwen, Van Tilburg, & Jonker, 2005) and their providers (Anderson, Fuller, & Dudley, 2007; Atwal, McIntyre, & Wiggett, 2012; Long-Sutehall et al, 2011; Sweeney & Doody, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Differing understandings of risk between professionals, patients and family carers are well established (Clarke, 2000;Clarke, Wilkinson, Gibb, Luce, & Williams, 2010;Mitchell & Glendinning, 2007) and these colliding perspectives shape planning for care home admission. Risk assessment and management are understood to be central to professional practice in healthcare (Alaszewski, Harrison, & Manthorpe, 1998;Manthorpe, Walsh, Alaszewski, & Harrison, 1995) and are influential determinants of decision-making, specifically influencing discharge destination (Atwal, McIntyre, & Wiggett, 2012).…”
Section: Riskmentioning
confidence: 99%